RELATIONSHIP AMONG PERSONAL SELF-ESTEEM, COLLECTIVE SELF-ESTEEM AND COMMUNITY PARTICIPATION - Sánchez Santa-Bárbara, Emilio (Anales de Psicología / Annals of Psychology, 1999)
A recent development of the study of self concept has lead to the emergence of ‘collective self-esteem’ (CSE) in addition to ‘personal self-esteem’ (PSE). While CSE is the degree in which an individual is aware of and evaluates his/her membership to groups or social categories, PSE is related to the positive or negative evaluation of personal (private or interpersonal) attributes. This paper reviews the relationships among both types of self-esteem and community participation. College students (n=154) were measured in these variables. The results show a high level of participation and membership to community associations. In addition, it was found a positive relationship between both types of self-esteem and between CSE and participation, but no relationship between PSE and participation. When compared members and non-members, CSE and all but one dimension indicated a significant higher self-esteem in members These results are considered from the point of view of Social Identity Theory and of Community Psychology.